Effects of uterine preservation on long-term subjective outcomes of sacrospinous ligament fixation for the treatment of pelvic organ prolapse. (September 2019) - Ng, Soo-Cheen; Tsui, Kwong-Pang; Huang, Litz; Chen, Gin-Den
Abstract: Objective: To evaluate the long-term subjective outcomes in women who underwent sacrospinous ligament fixation with and without uterine preservation for treatment of uterovaginal prolapse. Study design: Two hundred and ten women with POP-Q≧stage III uterovaginal prolapse, who underwent sacrospinous ligament fixation from January 1994 to December 2007 were included. Patient Global Impression of Improvement was used to assess the surgical outcome in July 2016. Primary outcome measures were subjective success rate and current satisfaction. Kaplan-Meier method and Cox proportional hazard model were used for analysis. Results: The mean follow-up was 13.3 years (range 8.5–22.6 years). One hundred and thirty-nine patients were successfully interviewed and analyzed. The cumulative subjective success rate was 88.5% and current satisfaction was 77.7%. The repeat surgery rate was 2.9%. There were no significant differences in subjective success (89% vs. 88%) or current satisfaction (78.1% vs. 77.3%) between uterine preservation (n = 64) and concomitant hysterectomy (n = 75). Kaplan-Meier analysis showed that sacrospinous ligament fixation with uterine preservation had a better subjective outcome at mid-term follow-up but was not significantly different compared with concomitant hysterectomy after long-term follow-up (P = 0.63). The adjusted HR of uterine preservation was 0.75 (95%CI: 0.22–2.12, P = 0.59). Conclusion: Sacrospinous ligament fixation with or without uterine preservation in the treatment of women with uterovaginal prolapse has no significant difference in long-term subjective outcomes and patient satisfaction.